Prenatal Diagnosis of Lesch-Nyhan Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The results of carrier and prenatal diagnosis for Lesch-Nyhan syndrome by carrier testing of 83 women and prenatal analysis of 26 pregnancies are reported from the Department of Molecular and Human Genetics, Baylor College of Medicine, Houston, TX.